Imagery and Meaning in Children's Poetry Anthology Letters from the Ocean - Kusumaningrum, Endah (International Proceedings of Nusantara Raya, 2023)
Children's poetry is an interesting form of literary work containing abstractions of words that have a child's point of view in which they contain experiences reflecting on the reality of life in the form of poetry. This study aims to describe the imagery and meaning contained in the Anthology of Children's Poetry Letters from the Ocean. The method used in this study is descriptive qualitative. Data collection is carried out by listening, reading, and recording techniques. Data grouping is carried out using reduction stages. The results obtained from this study were the discovery of visual imagery, auditory imagery, taste imagery, tactile imagery, and motion imagery. The meaning contained in the poetry anthology is described by a sense of pleasure, gratitude, and the depiction of a happy heart.